MACHADO DE ASSIS: “UMA EXCURSÃO MILAGROSA” - Salomoni, Rosane Saint-Denis (Organon, 2012)
The purpose of this work is to present a view about Machado’s shortstory “O país das Quimeras”, that was rewrote few years later as “Uma excursãomilagrosa” and reveal some aspects of the narrative that includes narrator’s strategiesand his characteristics. I also established hipertextual relations according to evidencessupported by Machado’s way of writing